2014
DOI: 10.3895/s1981-36862014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Produção Em Matriz Sólida E Caracterização Parcial Das Proteases De Cogumelo Comestível Da Floresta Amazônica

Abstract: ResumoEnzimas proteolíticas constituem um dos mais importantes grupos catalisadores, tem ampla utilização comercial e industrial. Entre essas, as proteases de origem fúngica apresentam vantagens como alta diversidade, fácil produção em larga escala e recuperação. O objetivo deste estudo foi avaliar a produção e caracterizar parcialmente proteases do extrato bruto de Pleurotus ostreatoroseus cultivado em substratos agroindustriais. A cultura matriz foi preparada em ágar batata dextrose acrescida de extrato de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
4
1
4
Order By: Relevance
“…However, the optimum activity was observed at pH 7.0, maintaining around 88% of activity at pH 6.0. These results are in agreement with the ones reported by Fonseca et al (2014) who cultivated P. ostreatoroseus on amazonic substrates (sawdust, açai seeds, cupuaçu exocarp, pineapple peel and pineapple pulp) and observed optimum activity of the enzymes at pH 6.0 to 7.0. The production of extracellular proteases from P. ostreatorouseus cultivated on DA is probably associated with the mushroom that needs to be hydrolyzed in different types of substrates as nutritional source of protein.…”
Section: Effect Of Ph and Temperature On Enzyme Activity And Stabilitysupporting
confidence: 83%
See 4 more Smart Citations
“…However, the optimum activity was observed at pH 7.0, maintaining around 88% of activity at pH 6.0. These results are in agreement with the ones reported by Fonseca et al (2014) who cultivated P. ostreatoroseus on amazonic substrates (sawdust, açai seeds, cupuaçu exocarp, pineapple peel and pineapple pulp) and observed optimum activity of the enzymes at pH 6.0 to 7.0. The production of extracellular proteases from P. ostreatorouseus cultivated on DA is probably associated with the mushroom that needs to be hydrolyzed in different types of substrates as nutritional source of protein.…”
Section: Effect Of Ph and Temperature On Enzyme Activity And Stabilitysupporting
confidence: 83%
“…L. citrinus presented high proteolytic activity in DF+RB 20 (52.40 U/mL) and low in DA+RB 10 (10.73 U/mL). The results of this study with P. ostreatoroseus were higher than the ones reported by Fonseca et al (2014), who observed significant proteolytic activity (7.89 U/mL) from P. ostreatoroseus using cupuaçu exocarp supplemented with 20% rice bran as substrate. Similar results were reported by Machado et al (2016) and Souza et al (2016) that cultivated L. citrinus on cupuaçu exocarp supplemented with litter and pineapple bark without supplementation, respectively.…”
Section: Proteolytic Activitycontrasting
confidence: 54%
See 3 more Smart Citations